Effectiveness and Safety of Adalimumab Biosimilars in Pediatric Psoriasis: A Multi-Center International Experience - Bertoli C; Torres T; Romita P; Stingeni L; Hansel K; Mastorino L; Ortoncelli M; Panzone M; Cruz MJ; Bianchi L; Zangrilli A; Musumeci ML; et al. (Psoriasis: Targets and Therapy)
Cristina Bertoli,1 Tiago Torres,2 Paolo Romita,3 Luca Stingeni,4 Katharina Hansel,4 Luca Mastorino,5 Michela Ortoncelli,5 Michele Panzone,5 Maria João Cruz,6 Luca Bianchi,7 Arianna Zangrilli,7 Maria Letizia Musumeci,8 Giuseppe Micali,8 Carlo Gerbino,8 Oriana Simonetti,9 Edoardo De Simoni,9 Caterina Longo,1,10 Emmanuel Mahé,11 Vito Di Lernia1 1Dermatology Unit, Arcispedale Santa Maria Nuova, Azienda USL-IRCCS di Reggio Emilia, Reggio Emilia, Italy; 2Department of Dermatology, Centro Hospitalar Universitário do Porto, Porto, Portugal; 3Department of Biomedical Science and Human Oncology, Dermatological Clinic, University of Bari, Bari, Italy; 4Dermatology Section, Department of Medicine, University of Perugia, Perugia, Italy; 5Dermatology Clinic, Department of Medical Sciences, University of Turin, Turin, Italy; 6Department of Dermatology and Venereology, Pediatrics, Centro Hospitalar Universitário de São João, Oporto, Portugal; 7Department of Dermatology, University of Rome Tor Vergata, Rome, Italy; 8Dermatology Clinic, University of Catania, Catania, Italy; 9Dermatological Clinic, Department of Clinical and Molecular Sciences, Polytechnic Marche University, Ancona, Italy; 10Department of Dermatology, University of Modena and Reggio Emilia, Modena, Italy and Skin Cancer Center, Azienda Unità Sanitaria Locale-IRCCS di Reggio Emilia, Reggio Emilia, Italy; 11Dermatology Department, Hôpital Victor Dupouy, Argenteuil, FranceCorrespondence: Vito Di Lernia, Dermatology Unit, Arcispedale Santa Maria Nuova, Viale Risorgimento 80, Reggio Emilia, 42123, Italy, Email vito.dilernia@ausl.re.itBackground: Many adalimumab biosimilars have been approved for the same indications as their originator (Humira ®). However, data on their efficacy and safety in children with psoriasis are scarce.Objective: To assess the effectiveness and safety of adalimumab biosimilars in a group of adalimumab-naïve patients and another group of patients who switched from originator adalimumab to biosimilars. The co-primary endpoints were the PASI absolute mean, PASI 75, and PASI 90 at 16, 24 and 52 weeks.Methods: In this 52-week, multi-center, non-interventional, observational, retrospective study, patients starting biosimilars in routine practice after January 2022 were enrolled at 10 sites across Italy, Portugal, and France. Disease activity scores such as the Psoriasis Area Severity Index (PASI) and safety data were captured during 12 months following adalimumab biosimilar initiation.Results: A total of 102 pediatric patients with psoriasis receiving adalimumab biosimilar therapy either as naïve (n = 72) or switching from originator adalimumab (n = 30) were enrolled. Median absolute PASI remained low at weeks 16, 24, and 52 in both groups (naïve 5.4, 4.3, 2.8; switching 2.6; 2.0; 1.4 respectively). PASI 75 response at weeks 16, 24, and 52 was observed in 41.7, 55.0, and 77.8% of patients in the naive group and 82.8%, 86.2%, and 92.6% of patients in the switch group. PASI 90 response at weeks 16, 24, and 52 was achieved by 23.3%, 26.7%, and 46.3% of patients in the naïve group and 58.6%, 65.5%, and 55.6% of patients in the switch group. Three patients discontinued biosimilars after the switch due to loss of efficacy. No emergency room visits or hospitalizations were observed during the study period and none of the patients experienced serious adverse effects.Conclusion: Adalimumab biosimilars showed a favorable effectiveness/safety profile in childhood psoriasis. Switching from reference adalimumab to biosimilars did not impact effectiveness and safety. A likelihood of discontinuation was noted in patients who switched from Humira to biosimilars.Keywords: treatment, psoriasis, children, effectiveness, safety, biologics, TNF-alpha